Finite Element Analysis of Perforated Cold-Formed Steel Section: Effects of Shear Behaviour - De’nan, Fatimah; Hashim, Nor Salwani; Lee, Kenth Zenth (Journal of Structural Monitoring and Built Environment, 2022)
This paper presents a numerical study on the shear behaviour of the steel framing system using a perforated section. The perforated steel section has a lower volume of steel, which causes the weight to decrease and lead to lower construction costs. However, perforation in steel will decrease the shear resistance of the steel framing system. The objective of this study was to investigate the shear behaviour of the perforated steel section comparing to the unperforated section in the steel framing system. Critical shear loading from a common steel framing system was obtained using Staad Pro software according to Eurocode Standard. Finite element analysis was performed and the structure capacity results were compared by using eigenvalue. Comparison were made between perforated sections and unperforated section in term of shear capacity and percentage of volume reduction. Perforation steel section with 8 diamond openings was selected with the percentage of shear buckling capacity difference from an unperforated section about 33.02% and 48.18% with circle openings. Shear buckling capacity reduced with the increasing number of web openings. Edge distance also affected the shear behaviour of plain channel section with web openings.